Learning traditional Malay folk song and tempo control by using an M-learning model designed for beginner pianists - Loo, Fung Ying; Loo, Fung Chiat; Chai, Khai Ern (2016)
Through observation and literature review, it is gathered that using conventional approaches in teaching traditional and folk music to the globalized and modernized society is a huge challenge. Nonetheless, the preservation of culture and traditional art forms is consistently encouraged by government and in the realm of education. This research developed a mobile-orchestra model in an M-learning approach with an attempt to bring forward an edutainment concept in generating interest in local folk songs. An M-learning music model using Malay folk song Dondang Sayang was designed, where the test focused on learning rhythmic subdivision and tempo stability. An experiment was carried out to test the learning outcome among respondents who are adult beginner piano students. The result shows that ability and interest to perform the designated set of rhythmic pattern was significantly higher using the M-learning model. In addition, the test shows that the model is a potential tool to develop awareness of traditional Malay folk song.